2000
DOI: 10.1002/(sici)1097-4652(200003)182:3<351::aid-jcp5>3.3.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A decreases the degradation of type I collagen in rat gingival overgrowth

Abstract: Cyclosporin A (CsA) is used as an immunosuppressive agent and its prominent side effect is the induction of fibrous gingival overgrowth. The purpose of this study was to investigate the effect of CsA on the type I collagen metabolism in the gingiva of rats fed a powdered diet either containing or lacking CsA. Immunohistochemical analysis revealed that type I collagen was more prevalent in the connective tissue of CsA-treated gingiva than in those of control rats on days 15, 30, and 55 after the start of feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…j o u r n a l o f o r a l b i o l o g y a n d c r a n i o f a c i a l r e s e a r c h 6 ( 2 0 1 6 ) 1 0 -1 7 collagen fiber in group IV, it was less than that of groups II and III; this is in agreement with Kataoka et al 34 as they noted reduction in collagen fiber phagocytosis by fibroblast after 30 days of CsA use before macroscopic detection of GO. CD163 antibody aids in identifying cells of monocyte/ macrophage lineage in normal and neoplastic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…j o u r n a l o f o r a l b i o l o g y a n d c r a n i o f a c i a l r e s e a r c h 6 ( 2 0 1 6 ) 1 0 -1 7 collagen fiber in group IV, it was less than that of groups II and III; this is in agreement with Kataoka et al 34 as they noted reduction in collagen fiber phagocytosis by fibroblast after 30 days of CsA use before macroscopic detection of GO. CD163 antibody aids in identifying cells of monocyte/ macrophage lineage in normal and neoplastic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that phenytoin and cyclosporin A inhibit production of the lysozomal proteinase cathepsin L, but not cathepsin B, by human gingival fibroblasts (Yamada et al, 2000). Cyclosporin may also inhibit phagocytosis of type I collagen in vitro and in vivo (Kataoka et al, 2000;Arora et al, 2001). Consistent results were found in cathepsin-L-deficient mice that exhibited enlarged gingival epithelial and connective tissues (Nishimura et al, 2002).…”
Section: Gingival Overgrowth and Diminished Tissue Resorptionmentioning
confidence: 94%
“…2), and severe inhibition was observed in cyclosporine A-induced gingival overgrowth. 25,26) Interestingly, type I collagen and collagenase mRNA expressions were significantly suppressed by cyclosporin A and nifedipine administration in these rat experimental models. 25,26) From these results, drug-induced gingival overgrowth is not due to the increased synthesis of type I collagen but the decreased degradation of type I collagen in gingival connective tissue through the reduction of collagen phagocytosis of fibroblasts.…”
Section: Synthesis and Degradation Of Type I Col-lagen In Drug-inducementioning
confidence: 71%
“…[36][37][38][39] These drug-induced gingival overgrowth is shown to be induced by the excessive accumulation of type I collagen in gingival connective tissue by immunohistochemical analysis with rat experimental models. 25,26) These disorders are therefore suitable to be considered as fibrosis in gingival connective tissue. "Gingival overgrowth" or "gingival enlargement" is the preferred term for all drug-related gingival lesions previously termed "gingival hypertrophy" or "gingival hyperplasia".…”
Section: Accumulation Of Type I Collagen In Gin-gival Connective Tissuementioning
confidence: 78%
See 1 more Smart Citation